Heat treatment induced phase transformations in zirconia and yttria-stabilized zirconia monolithic aerogels - Torres-Rodríguez, Jorge Alberto; Kalmár, József; Menelaou, Melita; Čelko, Ladislav; Dvořak, Karel; Cihlář, Jaroslav; Kaiser, Jozef; Győri, Enikő; Veres, Péter; Fabian, Istvan; Lázár, István (My University, 2019)
Monolithic, structurally stable zirconia (ZrO2) aerogels can be used in high temperature applications and as medical implants. The macroscopic properties of these solids can be fine-tuned by the appropriate thermal treatment of the amorphous aerogels. Herein, we investigate the thermally induced phase transitions of ZrO2 and yttria-stabilized zirconia (YSZ) monolithic aerogels. All aerogels were produced by an acid-catalyzed sol-gel technique and subsequent supercritical drying (SCD). A complete reaction mechanism is proposed for the formation of the wet gel network. Also, the phase transformations taking place during calcination were followed as function of temperature by in-situ X-ray diffraction measurements. Composition and size of the forming crystallites were calculated from the XRD data. Phase transition is controlled by the temperature-dependent growth of crystallite size during calcination up to 1200 °C. Both tetragonal and monoclinic zirconia form in pure ZrO2 aerogels, and a single tetragonal phase forms in YSZ aerogels.
Keywords: Aerogel; Heat treatment; Phase transformation; Yttria-stabilized zirconia; Zirconia